Prevalence of antimicrobial resistance in Haemophilus influenzae, Streptococcus pneumoniae, Moraxella catarrhalis and Streptococcus pyogenes: results of a multicentre study in Turkey - (:unkn) unknown (ELSEVIER SCIENCE BV, 2002)
The in vitro activities of several antimicrobial agents against clinical isolates of Streptococcus pneumoniae (283), Haemophilus influenzae (272), Moraxella catarrhalis (179) and Streptococcus pyogenes (256) were determined in a multicentre study with the participation of five hospitals from four cities in Turkey. Penicillin resistance in S. pneumoniae was evaluated using the E-test and the remaining agents by disk diffusion. For S. pneumoniae overall 25.8% of the isolates were intermediately and 3.9% were highly resistant to penicillin and resistance to chloramphenicol, azithromycin and trimethoprim/sulphamethoxazole (TMP/SMX) was 3.8, 2.1 and 55.4%,, respectively. Seven percent of H. influenzae produced P-lactamase and all were susceptible to cefotaxime and azithromycin; the highest rate of resistance, 23.5%, was for TMP/SMX. Eighty-one percent of M. catarrhalis isolates produced beta-lactamase, 18.4% were resistant to TMP/SMX and all were susceptible to sulbactam/ampicillin combination. Resistance to chloramphenicol and azithromycin of S. pyogenes was 2.2 and 1.9%, respectively. (C) 2002 Elsevier Science B.V. and International Society of Chemotherapy. All rights reserved.
Keywords: antimicrobial resistance; Haemophilus influenzae; Streptococcus pneumoniae; Moraxella catarrhalis; Streptococcus pyogenes; ANTIBIOTIC-RESISTANCE; UNITED-STATES; SUSCEPTIBILITIES; SURVEILLANCE; AMPICILLIN; COUNTRIES